1999
DOI: 10.1046/j.1365-2672.1999.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

New types of antimicrobial compounds produced by Lactobacillus plantarum

Abstract: . New types of antimicrobial compounds were identified in the culture filtrate of Lactobacillus plantarum VTT E-78076. Activity was detected in the low molecular mass fraction separated by gel chromatography. This fraction totally inhibited the growth of the Gram-negative test organism, Pantoea agglomerans (Enterobacter agglomerans) VTT E-90396. Characteristic compounds from this fraction were identified by GC/MS-analysis and the identification was confirmed using pure commercial reference compounds in identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(200 citation statements)
references
References 14 publications
5
191
0
4
Order By: Relevance
“…Similarly, it was found that Gram-positive Lactobacillus plantarum species also produced cyclic dipeptides, including cyclo(L-Phe-L-Pro), cyclo(L-Phe-trans-4-OH-L-Pro), and cyclo(Gly-L-Leu), which exhibited antifungal activity (28,46). Although the fungal inhibitory properties of cyclo (L-Tyr-L-Pro) and cyclo(L-Phe-L-Pro) produced by L. reuteri RC-14 have yet to be tested, neither of the two compounds displayed toxicity against S. aureus (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, it was found that Gram-positive Lactobacillus plantarum species also produced cyclic dipeptides, including cyclo(L-Phe-L-Pro), cyclo(L-Phe-trans-4-OH-L-Pro), and cyclo(Gly-L-Leu), which exhibited antifungal activity (28,46). Although the fungal inhibitory properties of cyclo (L-Tyr-L-Pro) and cyclo(L-Phe-L-Pro) produced by L. reuteri RC-14 have yet to be tested, neither of the two compounds displayed toxicity against S. aureus (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…listed in Table I were determined against the eight moulds by the disc diffusion method 19,23 . Moulds were incubated for 5 days at 25°C.…”
Section: Disc Diffusion Assaymentioning
confidence: 99%
“…Gram-negative bacteria has been reported 19 . It is possible that the P. pentosaceus strain used in this study produced such antimicrobial compounds.…”
Section: Cultures (Code Number) Original Culture Numbers Sourcementioning
confidence: 99%
“…According to the classification advanced by Orla-Jensen, the genus Lactobacillus was further divided into three subgeneraThermobacterium, Streptobacterium and Betabacterium in accordance with the observed optimal growth temperature characteristics and hexose fermentation pathways [1]. Lactobacilli are gram positive, rod shaped, catalase negative bacteria and could safely be considered the most important of all lactic acid bacteria owing to their role in various food and feed fermentations, production of many important metabolites, and owing to their role in the prevention of food spoilage, intoxication and infection by acting as antagonists against other pathogens by the production of antimicrobials [2][3][4]. With the growing population, and the demand exerted on the quality fermented dairy products, Lactobacilli have increasingly been under the research scanner for the last two decades.…”
Section: Introductionmentioning
confidence: 98%